2015
DOI: 10.1080/14786419.2015.1004674
|View full text |Cite
|
Sign up to set email alerts
|

A new butenolide cinnamate and other biological active chemical constituents fromPolygonum glabrum

Abstract: Phytochemical investigation of the methanol extract of the aerial parts of Polygonum glabrum afforded one new natural product (-)-2-methoxy-2-butenolide-3-cinnamate (1) along with six known compounds, β-hydroxyfriedalanol (2), 3-hydroxy-5-methoxystilbene (3), (-) pinocembrin (4), sitosterol-(6'-O-palmitoyl)-3-O-β-D-glucopyranoside (5), (-) pinocembrin-5-methyl ether (6) and sitosterol-3-O-β-D-glucopyranoside (7). Compound 1 showed promising in vitro anti-HIV-1 activity against primary isolates HIV-1(UG070) (X4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The present study is also in accordance with the previous reports since an increase in LDH and SGOT enzymes are observed in isoproterenol treated groups. [2,3-dihydroxy isodrimeninol] etc, administration of this extract might prevent the leakage of biomarkers in to blood stream by stabilizing the membranes [13]. The quantity and composition of lipids in the myocardium is also a determinative factor for development of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study is also in accordance with the previous reports since an increase in LDH and SGOT enzymes are observed in isoproterenol treated groups. [2,3-dihydroxy isodrimeninol] etc, administration of this extract might prevent the leakage of biomarkers in to blood stream by stabilizing the membranes [13]. The quantity and composition of lipids in the myocardium is also a determinative factor for development of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…The methanol extract showed maximum antimicrobial activity against pathogens such as Staphylococcus aureus, Micrococcus luteus, Candida tropicalis etc [12]. Substantial literature survey suggested that many phytoconstituents such as (2)-2-methoxy-2-butenolide-3cinnamate, beta-hydroxyfriedalanol, 3-hydroxy-5-methoxystilbene, pinocembrin, sitosterol-(6α-O-palmitoyl)-3-O-β-Dglucopyranoside, pinocembrin-5-methyl ether and sitosterol-3-O-βDglucopyranoside were isolated from Polygonum glabrum [13]. Other flavonoids (avicularin, rhamnetin, diosmetin, cyanidin 3 5-diglucoside, delphinidin 3,5, diglucoside) and sesqueterpene diesters were isolated from methanol extract of leaves and flowers of Polygonum glabrum [14,15]…”
Section: Ecrosis In Ratsmentioning
confidence: 99%
“…Rosmarinic acid is a polyphenolic compound from the plant Prunella vulgaris, usedfor the treatment of isolated HIV [378]. From Polygonum glabrum, various bioactive constituents with antiretroviral activities have been reported, e.g., (-)-2-methoxy-2-butenolide-3-cinnamate, pinocembrin (96), 3-hydroxy-5-methoxystilbene (97), sitosterol-3-O-β-D-glucopyranoside, and pinocembrin-5-methyl ether [379]. Actein (98) from the rhizomes of Cimicifuga racemosa, possessed a significant activity against HIV [380].…”
Section: Miscellaneous Plant-based Anti-hiv Agentsmentioning
confidence: 99%
“…Rosmarinic acid is a polyphenolic compound that is isolated from the plant Prunella vulgaris, is used for the anti-HIV potential [366]. ether [367]. Actein (98) is extracted from the rhizomes of plant Cimicifuga racemosa, has possessed significant activity against the HIV virus [368].…”
Section: Miscellaneous Plants Used As Anti-hiv Agentsmentioning
confidence: 99%